2014
DOI: 10.1080/14786435.2014.965235
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two approaches for the treatment of Gutzwiller variational wave functions

Abstract: In this work, we analyse the variational problem emerging from the Gutzwiller approach to strongly correlated systems. This problem comprises two main steps: evaluation and minimization of the ground state energy W for the postulated Gutzwiller Wave Function. We discuss the available methods for evaluating W , in particular the recently proposed diagrammatic expansion method. We compare the two existing approaches to minimize W : the standard approach based on the effective single-particle Hamiltonian and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 44 publications
(116 reference statements)
0
30
0
Order By: Relevance
“…To account for nonlocal spatial correlations in finite dimensions, higher orders of the expansion (k > 0) are systematically incorporated in Eq. (4) and expectation values of the products of the operators are evaluated diagrammatically [25,26,[42][43][44][45][46][47]. By construction [25], the convergence of the sum with respect to k is reached relatively quickly, and here we found that k = 4 is already satisfying (see the Supplemental Material [48]).…”
mentioning
confidence: 83%
“…To account for nonlocal spatial correlations in finite dimensions, higher orders of the expansion (k > 0) are systematically incorporated in Eq. (4) and expectation values of the products of the operators are evaluated diagrammatically [25,26,[42][43][44][45][46][47]. By construction [25], the convergence of the sum with respect to k is reached relatively quickly, and here we found that k = 4 is already satisfying (see the Supplemental Material [48]).…”
mentioning
confidence: 83%
“…40, it is equivalent to the method based on the Lagrange multipliers which in turn guarantees the preservation of the statistical consistency during the minimization procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Jastrow intersite factors 53 . Here we use an alternative method of evaluating the expectation values for GWF, namely a systematic dia- grammatic expansion for the Gutzwiller wave function (DE-GWF) [54][55][56][57][58] . This method was formulated initially for the Hubbard model in two dimensions in the context of Pomeranchuk instability 54 , and applied subsequently to the description of high-temperature superconductivity for the Hubbard 55,58 and the t-J 56 models.…”
Section: Introductionmentioning
confidence: 99%